2020
DOI: 10.3390/ma13173837
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure and Fracture Behavior of Carbon Nanofiber-Reinforced Cement Using Nanoscale Depth-Sensing Methods

Abstract: In recent years, carbon nanofibers have been investigated as a suitable reinforcement for cementitious composites to yield novel multifunctional materials with improved mechanical, electrical, magnetic, and self-sensing behavior. Despite several studies, the interactions between carbon nanofibers and Portland cement hydration products are not fully understood, with significant implications for the mechanical response and the durability at the macroscopic lengthscale. Thus, the research objective is to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
5
4
0
Order By: Relevance
“…3. Similar to our values of Young's modulus were obtained as a result of studies [7], where it was also established that the presence of carbon nanofibers affects the stochastic distribution of the macroscopic Young's modulus, causing a shift towards higher values (29.66 GPa for simple Portland cement, 31.43 GPa for cement + 0.1 wt% CNT and 36.12 GPa for cement + 0.5 wt% CNT). 4.…”
Section: Analysis Of Research Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…3. Similar to our values of Young's modulus were obtained as a result of studies [7], where it was also established that the presence of carbon nanofibers affects the stochastic distribution of the macroscopic Young's modulus, causing a shift towards higher values (29.66 GPa for simple Portland cement, 31.43 GPa for cement + 0.1 wt% CNT and 36.12 GPa for cement + 0.5 wt% CNT). 4.…”
Section: Analysis Of Research Resultssupporting
confidence: 90%
“…2. Our position on the containment of cracking by carbon fibers at the nano-level coincides with the studies of Ange-Therese Akono [7,16], which show that carbon nanofibers fill nanopores and connect grains of calcium hydrates (C -S -H), which leads to the effect of bridging and facilitating load transfer, individual CNTs are embedded in hydration products and delay nanocracks. Also in [17], SEM images are demonstrated that confirm the effects of the formation of bridges that transfer the load along nano-and microcracks.…”
Section: Analysis Of Research Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Carbon nanofiber reinforced concrete is a composite of good performance, with ordinary concrete as the base material and carbon nanofiber as the reinforced material [20][21][22][23]. Compared with ordinary concrete, carbon nanofiber reinforced concrete was greatly improved in not only the mechanical properties and durability [22][23][24][25][26] but also the dielectric properties [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%